Global civil society advocacy alliances and networks in the changing terrain of global governance and development : a critical inquiry into the politics and dynamics in crafting and operations of the Global Action against Poverty (GCAP) - Mati, Jacob Mwathi (My University, 2009)
The last few decades have witnessed the emergence of global civil society advocacy networks as major players in global governance. This research aimed at using a case study of GCAP in critically analysing the politics and dynamics of crafting a global civil society advocacy alliance. Specifically, the study aimed to: a) identify, analyse, and document GCAP’s experiences, strategies and challenges in trans-national networking and advocacy; b) generate knowledge on recent developments in global civil society networking and advocacy. The study analyses the study phenomenon using two central features of GCAP: networking and advocacy. Chapter one attempts to give a background of the study and also discusses the methods used. Chapter two lays the theoretical framework and operationalises the concepts explored in the study. The report argues that alliances are very different from ‘normal’ forms of organisations because they are made up of diverse forms of organisations, coming together voluntarily to achieve a specific purpose. They are therefore, by their very nature, complex, unstable, and difficult to co-ordinate. Chapters Three and Four look at such intricacies and complexities of crafting and operations of global advocacy networks. I conclude this research arguing that despite challenges in alliances building and operations, global civil society organisations will still need to network if they are to remain relevant and effective in current global governance context. It is only in their unity that they will be able to confront their common challenges.
Keywords: Global civil society; Global governance; Poverty